The Academic Faltering of Orphan Students in the Quarantine of Covid-19 - Jabbar Frayyeh Shraida (Newinera Publisher, 2022)
The research objectives are there individual differences between the sample members according to gender, Limitations of the Study Curriculum book for first grade reading in Iraq for 2020-2021 academic years, the sample A sample (400) of the current research was selected from male and female teachers in Baghdad who expressed a desire to answer the research questions and The research tool: An exploratory question that was presented to teachers, “What are the reasons for students, ' failure to a study from your point of view, and 30 reasons were collected, Are there individual differences between the sample members according to the gender variable. It was found there are no individual differences between the Ganders and the reasons are known to them.